The influence of COVID-19 on the antibiotic consumption in a tertiary care hospital in Belgrade (Serbia) - Milos Gostimirovic; Predrag Savic; Teodora Vitorovic; Jovana Rajkovic; Ana Bukarica; Ljiljana Gojkovic Bukarica (Journal of Global Antimicrobial Resistance)
BACKGROUND: Regardless of COVID-19 being a viral disease, many initial protocols advised prescription of broad-spectrum antibiotics, which was supported by frequently confirmed secondary bacterial infection in patients. Overuse and/or misuse of antibiotics were already noticed in April 2020, which raised concerns of increased antimicrobial resistance. The aim of this study is to determine whether the COVID-19 pandemic has influenced the trend of antibiotic consumption in inpatient settings in a tertiary health care center, Belgrade, Serbia, between 1.4.2019-1.4.2022. METHODS: The consumption of antibiotics was calculated as the defined daily dose (DDD) per 100 patient-days (PD). We compared consumption by the specific ATC and AWaRe classification. PD was calculated as a ration of the number of inpatient days to the total number of patient admissions. RESULTS: During 1.4.2019-1.4.2020, 1.4.2020-1.4.2021 and 1.4.2021-1.4.2022. consumption of following antibiotics were significantly (p<0.05) increased: cephalosporins (ceftriaxone: 20.75, 25.41 and 26.25; cefixime 1.21, 1.23 and 6.12), macrolides (azithromycin 1.42, 4.75, 5.21), carbapenems (meropenem: 2.8, 13.01 and 16.81; imipenem: 0.85, 0.89 and 3.46), tigecyclin (0.86, 2.8 and 2.9), and vancomycin (1.29, 6.63 and 9.2) /all units in DDD/100 patient-days. The consumption of amikacin (2.49, 1.12 and 2.01), ceftazidime (1.33, 1.01 and 0.5) and erythromycin (0.02, 0.02 and 0.01) were decreased /all units in DDD/100 patient-days. CONCLUSIONS: COVID-19 might have caused increased consumption of numerous antibiotics, especially cephalosporins (ceftriaxone) and carbapenems (meropenem). This may be due to high percent of secondary bacterial infection in COVID-19 patients or, more likely, excessive antibiotic (mis)use, especially in mild form of COVID-19 disease.